The burden of group A Streptococcus (GAS) infections: The challenge continues in the twenty-first century - Aswin Thacharodi; Saqib Hassan; Avadh Vithlani; Tawfeeq Ahmed; Sanjana Kavish; Nicole-Mae Geli Blacknell; Ali Alqahtani; Arivalagan Pugazhendhi (iScience)
Summary: Streptococcus pyogenes is a Gram-positive bacterium, also known as Group A Streptococcus (GAS), that has become a significant threat to the healthcare system, infecting more than 18 million people and resulting in more than 500,000 deaths annually worldwide. GAS infection rates decreased gradually during the 20th century in Western countries, largely due to improved living conditions and access to antibiotics. However, post-COVID-19, the situation has led to a steep increase in GAS infection rates in Europe, the United States, Australia, and New Zealand, which triggers a global concern. GAS infections are normally moderate, with symptoms of fever, pharyngitis, and pyoderma; nevertheless, if left untreated or with continued exposure to GAS or with recurring infections it can result in fatal outcomes. GAS produces a variety of virulence factors and exotoxins that can lead to deadly infections such as necrotizing fasciitis, impetigo, cellulitis, pneumonia, empyema, streptococcal toxic shock syndrome, bacteremia, and puerperal sepsis. In addition, post-immune mediated disorders such as post-streptococcal glomerulonephritis, acute rheumatic fever, and rheumatic heart disease contribute to extremely high death rates in developing nations. Despite substantial research on GAS infections, it is still unclear what molecular pathways are responsible for their emergence and how to best manage them. This review thus provides insights into the most recent research on the pathogenesis, virulence, resistance, and host interaction mechanisms of GAS, as well as novel management options to assist scientific communities in combating GAS infections.